Production and evaluation study for an oil with dissolved associated gas field in the Pannonian Depression - Grigoraş, Ioan Dan (My University, 2012)
The work targets are: - additional data analysis, - geological model update, - resources and reserves reevaluation in order to be confirmed, - optimum production scenario set up, - discounted cash flow analysis.

Celem pracy są: - analiza danych dodatkowych, - uzupełnianie modelu geologicznego, - potwierdzające szacowanie złóż i zasobów, - optymalny zestaw produkcyjny, - analiza kosztów.
Badanie i szacowanie produkcji ropy naftowej z towarzyszącym rozpuszczonym gazem ziemnym na złożach Niziny Panońskiej
AGH Drilling, Oil, Gas
Keywords: non-associated gas; oil; condensate; natural gas; reservoir; production; niezwiązany gaz ziemny; ropa naftowa; wells; gaz ziemny; złoża; resources; produkcja; otwory; reserves; zasoby; geologia; geology; kondensat